Ukraine’s Euromaidan in Turkish Media - Maksymenko, O. (Социология: теория, методы, маркетинг, 2016)
The author, who is working at the moment as a translator and contributor to a Turkish news web site, has made an attempt to study how the Euromaidan events were represented in Turkish mass media.